Analisis Perubahan Kandungan Lemak Padat , Asam Lemak Trans Dan Komposisi Trigliserida Pada Pembuatan Lemak Pengganti Mentega Coklat Melalui Metode Blending Dibandingkan Interesterifikasi RBDPS Dengan RBDPKO: Analysis of Changes in Solid Fat Content, Trans Fatty Acids and Triglyceride Compositions in the Manufacture of Substitute of Chocolate Butter Through Blending Method Compared to Interesterification of RBDPS with RBDPKO (Talenta Conference Series: Science and Technology (ST), 2018)
Lemak pengganti mentega coklat (CBS) dalam industri dapat dihasilkan melalui proses hidrogenasi parsial minyak cair, blending maupun interesterifikasi lemak padat dan minyak cair. Nilai kandungan asam lemak trans (TFA) dan kandungan lemak padat (SFC) merupakan parameter yang penting diuji dalam memenuhi kwalitas dari lemak tersebut sebagai edible oil. Dalam penelitian ini dilakukan metode blending dibandingkan dengan interesterifikasi menggunakan katalis natrium metoksida antara lemak padat RBDPS dengan RBDPKO pada rasio 90:10, 80:20, 70:30, 60:40, 50:50, 40:60, 30:70, 20:80 dan 10:80 (b/b) untuk menghasilkan lemak pengganti mentega coklat. Dari penelitian ini diperoleh lemak pengganti coklat hasil blending maupun interesterifikasi antara RBDPS dengan RBDPKO paling sesuai pada rasio 20:80(b/b) dengan nilai SFC dari hasil analisis menggunakan fulse-NMR masing-masing 1,06% dan 1,10% pada suhu 35OC dan nilai TFA hasil analisis KGC masing-masing 0,14% dan 0,13% sedangkan perubahan komposisi trigliserida dominan terjadi pada TG-C48, TG-C50, TG-C52 dan TG-C54 Chocolate butter substitute (CBS) fat in the industry can be produced through the process of partial hydrogenation of liquid oil, blending and interesterification of solid fat and liquid oil. The value of trans fatty acid content (TFA) and solid fat content (SFC) are important parameters to be tested in meeting the quality of these fats as edible oil. In this study, a blending method was compared with interesterification using a sodium methoxide catalyst between RBDPS solid fat and RBDPKO at a ratio of 90:10, 80:20, 70:30, 60:40, 50:50, 40:60, 30:70, 20 : 80 and 10:80 (b/b) to produce substitutes for chocolate butter fat. From this study, it was found that chocolate substitute fat from blending and interesterification between RBDPS and RBDPKO best matched the ratio of 20:80 (b/b) with the SFC value from the analysis using Fulse-NMR of 1.06% and 1.10% correspondingly. 35°C temperature and TFA value from KGC analysis were 0.14% and 0.13% respectively while the change in dominant triglyceride composition occurred in TG-C48, TG-C50, TG-C52 and TG-C54.
Keywords: mentega coklat; asam lemak trans; kandungan lemak padat; interesterifikasi